2013
DOI: 10.1007/s10735-013-9504-9
|View full text |Cite
|
Sign up to set email alerts
|

ZNRF3 acts as a tumour suppressor by the Wnt signalling pathway in human gastric adenocarcinoma

Abstract: E3 ubiquitin ligases regulate a variety of biological processes through the ubiquitin-proteasome system, together with ubiquitin activating enzyme E1 and ubiquitin-conjugating enzyme E2. Previous studies have demonstrated that zinc and ring finger 3 (ZNRF3), which belongs to the E3 ubiquitin ligases family is involved in the Wnt signalling pathway, which plays an important role in causing cancer. However, the expression and function of ZNRF3 in human gastric adenocarcinoma still remains unclear. Immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 26 publications
2
34
0
3
Order By: Relevance
“…These findings reveal a novel mechanism of miR-146b-5p mediated induction of EMT and suggest that ZNRF3 plays a tumor suppressor role in PTC. A similar role for ZNRF3 was demonstrated in human gastric adenocarcinoma in a recent study that showed that ZNRF3 inhibits gastric cancer cell growth and promotes apoptosis through the modulation of the Wnt/β-catenin signaling pathway [23]. Mutations in ZNRF3 and its homolog RING finger 43 (RNF43) have been linked to pancreatic ductal adenocarcinoma and mucinous ovarian tumors [24,25] confirming the role of these ubiquitin ligases as tumor suppressors.…”
Section: Discussionmentioning
confidence: 60%
“…These findings reveal a novel mechanism of miR-146b-5p mediated induction of EMT and suggest that ZNRF3 plays a tumor suppressor role in PTC. A similar role for ZNRF3 was demonstrated in human gastric adenocarcinoma in a recent study that showed that ZNRF3 inhibits gastric cancer cell growth and promotes apoptosis through the modulation of the Wnt/β-catenin signaling pathway [23]. Mutations in ZNRF3 and its homolog RING finger 43 (RNF43) have been linked to pancreatic ductal adenocarcinoma and mucinous ovarian tumors [24,25] confirming the role of these ubiquitin ligases as tumor suppressors.…”
Section: Discussionmentioning
confidence: 60%
“…These molecular changes seem to be required to drive early carcinogenesis events in the stomach, a hypothesis that is supported by studies showing that GSK3b phosphorylation and inactivation is associated with cancer progression in gastric cancer [105] . Different studies have shown downregulation-in occasion by unspecified mechanisms-of various negative regulators of the Wnt/b-catenin signaling involved in proliferation and invasion in gastric cancer, including sFRP, Sox7, Sox10, Sox17, HSulf-1, RACK1, ZNRF3 and OSR1 [78,[106][107][108][109][110][111][112][113] . Some Wnt-target genes, such as Dkk-1, Axin, Nemo kinase, etc., have shown to cause inhibition of Wnt signaling itself [114,115] .…”
Section: Loss Of Wnt Repressor Function In Gastric Cancermentioning
confidence: 99%
“…Many studies have indicated that Wnt/b-catenin and Hedgehog signaling pathways are important in the regulation of tissue growth and development. Thus, dysregulated Wnt/b-catenin signaling is involved in many cancers including colorectal, hepatocellular, and gastric cancers and also hereditary diseases [4][5][6]. Wnt proteins bind to receptors of the Frizzled family on the cell surface and regulate the turnover of the b-catenin transcription cofactor and regulate gene expression programs that are relevant for organism development [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There are several types of E3-ubiquitin ligases, which control the levels and turnover of different proteins in multiple subcellular locations, and their deregulation can contribute to various diseases including carcinogenesis [21]. ZnRF3 has been shown to inhibit Wnt signaling by enhancing the breakdown of frizzled and LRP6 [18], and overexpression of ZnRF3 was found to induce apoptosis by lowering the protein levels of b-catenin and TCF-4 [5]. Also expression of ZnRF3 was found to be reduced in gastric cancers compared to the normal surrounding tissue [5] and mutated in pancreatic cancer [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation